The Gold Eaters - Ducca Durán, Isabel (2023)
The paper reviews the metaphor of gold in different testimonies of the conquest of America to carry out an ideological analysis. These testimonies are considered from the ideological perspective of critical discourse analysis and the fetishism theory of historical materialism, aiming to establish the idolatry of gold within the framework of capitalist relations of production. In conclusion, a parallelism is established between the obsession with gold and extractive projects and their consequences for peasant territories and native communities.